PENGARUH INPUT PRODUKSI DAN PELAYANAN IRIGASI TERHADAP PRODUKSI PADI SAWAH DI DAERAH IRIGASI WATATU KECAMATAN BANAWA SELATAN KABUPATEN DONGGALA - Gazali Fathadewang (Agroland: Jurnal Ilmu-ilmu Pertanian, 2016)
The research was conducted in South Banawa Watatu village of Donggala district. The purpose of this study was to determine the effect of production inputs and irrigation service quality on rice production in irrigated areas of Watatu. Total population of 144 farmers were divided into two (2) categories: (1) 92 people who pay irrigation service fee; and (2) 52 people who do not pay the service fees.  About 25% of people from each category was selected, so the total respondents was 36 people Data was analyzed using a multiple linear analysis with Cobb Douglas production function model. The results showed that, independent variables (Xi) consisting of land area (X1), seeds (X2), urea (X3), NPK (X4), and labor (X5) and dummy quality of irrigation service (D), simultaneously had significant effect on the dependent variable or the output (Y). The determinant coefficient value (R2) of 0.975 suggesting that 97.5%ofthe fluctuation in rice production (Y) under irrigation in Watatu can be explained by the independent variables (Xi), while 2.5% was caused by other factors not included in the model.  Partially, the land area (X1), the use of urea (X3), the use of NPK fertilizer (X4) and the dummy irrigation service quality (D) significantly affected the rice production (Y) whereas the remaining production inputs had no significant effect on the rice production (Y). The rice production under the irrigation service quality of available category was 63.89% whereas under that of unavailable category was 36.11% indicating that the farmers consciously have the will and desire to pay the irrigation service fees for eachplanting season.Keywords : Input production, irrigation, quality of service, wetland rice.